Role of DNA damage and repair in radiation cancer therapy: a current update and a look to the future. (1st November 2020) - Liu, Jingya; Bi, Kun; Yang, Run; Li, Hongxia; Nikitaki, Zacharenia; Chang, Li
Abstract: Radiation Therapy (RT), a widely used modality against cancer, depends its effectiveness on three pillars: tumor targeting precision, minimum dose determination and co-administrated agents. The underlying biological processes of the latter two pillars are DNA damage and repair. Hopefully, Radiation treatment has nowadays been improved a lot, in terms of tumor targeting precision as well as in minimization of side effects, by reducing normal tissue radiation exposure and therefore its occurred toxicity. Normal tissue toxicity is a major risk factor for induction of genomic instability which may lead to secondary cancer development, due to the radiation therapy itself. We discuss, in this review, the biological significance of IR-induced complex DNA damage, which is currently accepted as the definite regulator of biological response to radiation, as well as the regulator of the implications of this IR signature in radiation therapy. We unite accumulating evidence and knowledge over the last 20 years or so on the importance of radiation treatment of cancer. This radiation-based therapy comes unfortunately with a deficit and this is the radiation-induced genetic instability which can fuel radiation toxicity, even several years after the initial treatment on patients through the activation of DNA damage response (DDR) and the immune system.